Students Interest In Online Learning: Minat Mahasiswa Terhadap Perkuliahan Online - Indra Sholehudin; Dedi Kurnia (Journal of Physical and Outdoor Education, 2022)
This study aims to determine how well students are interested in online lectures. The research method used is descriptive method through a survey approach. The instrument used in this study was a closed type of questionnaire. The participants in this study were students of STKIP Pasundan as many as 20 people using a sampling technique that was incidental sampling. the results of this study that student interest in online learning at STKIP Pasundan is moderate by 40% of students interested in participating in online learning. so educators must be more creative in using online learning media so that students are more enthusiastic in online learning in an already modern era that always uses digital technology